S132 Chronic Bronchitis, Pulmonary Function, and Occupational Exposure in Framingham Heart Study. (19th November 2012) - Liao, SY; Lin, X; Christiani, DC
Abstract : Introduction: Occupational exposure to dust, gases and fumes has been associated with chronic airway disease or poor lung function in several workforce based studies. However, workforce studies may underestimate such associations because of healthy worker effect confounding bias. We conducted a community-based study that used a more generalised populations of individuals and less susceptible to healthy worker effect. We investigated the associations between the self-reported occupational exposure and chronic bronchitis, as well as pulmonary function testing. Methods: The study population is the Third-Generation cohort from Framingham Heart Study with a total of 3, 894 participants. We used participants' examination of FEV1, FEV1/FVC, chronic bronchitis (based on self reported symptoms) as outcomes. Occupational exposure was assessed by self-reported exposure to vapours, gas, dust, or fumes at work. Gender, age, height, pack-years, and smoking status were used as covariates in our analysis. We used linear mixed effect models for continuous outcomes and generalised estimating equations for dichotomous outcomes due to the family structure. Results: There are 1, 745 participants reporting occupational exposure at work and 2, 149 participants reporting no occupational exposure. The association of occupational exposure on the FEV1 and FEV1/FVC was not significant in this cohort. However, self-reported occupational exposure was associated with a risk of chronic bronchitis after controlling for covariates (OR 1.55, 95% CI 1.19 to 2.01). Current smoking was associated with a greater risk of chronic bronchitis after controlling for covariates (OR 3.20, 95% CI 2.37 to 4.32). Those with combined occupational and smoking exposure had a 5 fold increased risk of chronic bronchitis compared those with neither occupational nor smoking exposure. Conclusions: Occupational exposure is significantly associated with chronic bronchitis. In addition to preventing smoking exposure, preventive strategies should be taken by clinicians and health policy-makers to reduce occupational exposures in workplace.